SUN-167 Treatment Considerations for a Healthy Pregnancy in Women with Classical Congenital Adrenal Hyperplasia (CAH) - Calzia, Megan (J Endocr Soc, 2020)
Background: CAH is caused by an enzyme deficiency involved in cortisol synthesis leading to an increase in ACTH. Increased ACTH causes elevated levels of steroid hormone precursors & chronic stimulation of the adrenal glands resulting in hyperplasia. The most common form of CAH is due to 21OH deficiency (21OHD) with the classic, salt-wasting form causing glucocorticoid & mineralocorticoid deficiency & androgen excess. Poorly controlled CAH causes increased production of androgens & progesterone & decreased fertility. Fertility in woman with 21OHD can be challenging due to decreased sexual interest & anatomical abnormalities. Despite these challenges, the pregnancy rate is not significantly lower in women with well controlled 21OHD. However, as these patients are uncommon recommendations for pregnancy can be challenging for endocrinologists. Clinical Case: A 27-year old G0P0 female with classic, salt losing CAH presented to discuss pregnancy. Her medications were hydrocortisone 10mg qAM & 5mg qHS & fludrocortisone 0.1mg daily. She denied symptoms of dehydration, nausea, vomiting, dizziness, or fatigue. She was diagnosed with CAH while in-utero & started on steroid therapy after birth. She did not require any surgical genital reconstruction. Menarche occurred at age 11 and she had regular menses every 35-40 days, with no evidence of excessive androgen exposure including excess body hair, deepening of her voice, or cliteromegaly. On physical exam she was normotensive & had no evidence of virilization or cushingoid features. She exhibited minor darkening of the palmar creases. Her labs were significant for free testosterone of 9.1 pg/ml (0.2-5.0 pg/ml), total testosterone of 115 ng/dl (2-45 ng/dl), ACTH of 780 pg/ml (6-50 pg/ml), androstenedione of 636 ng/dl (41-262 ng/dl), & 17 OHP of 1560 ng/dl (15-290 ng/dl). Her hydrocortisone dose was increased to 20 mg qAM & 10 mg qHS & fludrocortisone 0.1mg daily was continued. Our objectives were to normalize the androgen level & suppress serum progesterone to less than 2 nmol/L. If the objectives were not reached she would be converted to prednisone BID. Conclusion: Endocrine providers are the primary resource for fertility recommendations for 21OHD patients & must understand the challenges in this very rare group of patients. Collaboration with the perinatologist is crucial for success. The goals of preconception endocrine assessment in a patient with classic CAH are to adjust hormone therapy to ensure optimal endocrine milieu for conception & risk assessment of having a child affected with 21OHD. The patient will need a higher dose of fludrocortisone during the later part of pregnancy. Counseling that stress doses of glucocorticoids for intercurrent illness and during labor and delivery are required for both the patient and the obstetrician.